RISE: The challenge of sustaining improvements in patient medication adherence / Dr Nur Wahida Zulkifli - Zulkifli, Nur Wahida (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
Improved patient adherence to medications is a challenge for healthcare workers, particularly pharmacists. Adherence is the condition when patients take their medication as directed for controlling chronic conditions, treating acute conditions, and overall long-term health and wellbeing. If a patient does not adhere to their medications, it can cause a serious threat to their health as well as a significant financial burden not only to the patients itself but also to the government.